Melville's gravity: necessity, art, democracy. Issue 11 (2nd November 2021) - Greiman, Jennifer
ABSTRACT: This essay examines the aesthetics of gravity across Herman Melville's prose and poetry to argue that, rather than a figuration of irresistible necessity, the law of gravitation introduces unanticipated contingencies and modes of action into Melville's work. Building on the insights of scholars who have identified the philosophical significance of thrownness and fallenness in Melville's writing, this essay argues that the force of gravity also foregrounds aesthetics and politics – specifically the politics of abolition and war. Reading Melville's work alongside that of Frederick Douglass, this essay argues that both writers escape what Hannah Arendt describes as the fallacy of mathematic metaphors for political action. In emphasising figural elasticity, and not literal force, in gravitational pull, both Melville and Douglass find in it a surprising source of militant democratic potential.